Sexual dissatisfaction and associated factors in a sample of patients on antiretroviral treatment in KwaZulu-Natal, South Africa - Karl Peltzer (South African Journal of Psychiatry, 2011)
Background: Sexual expression affects physical, mental and social well-being. There is a lack of understanding on sexual problems among patients on antiretroviral treatment in Africa.